Complete chloroplast genome sequence of Gypsophila pacifica Kom. (Caryophyllaceae) - Sung Kyung Han; Tae-Im Heo; Byeong-Joo Park; Sung-Hyuk Park; Sang Hoon Che (Journal of Asia-Pacific Biodiversity)
Gypsophila pacifica Kom. (1916) is a perennial herb native to Korea, China, and Russia, known for its ornamental and medicinal value. However, our understanding of its genomic information remains inadequate. In this study, we determined its complete chloroplast genome (cp) sequence. The cp genome of G. pacifica is 152,827 base pairs (bp) long with a guanine-cytosine content of 36.4%. It consists of a large single-copy region of 83,850 bp, a small single-copy region of 17,329 bp, and two inverted repeat regions of 25,824 bp each. A total of 130 genes were identified in the genome, including 85 protein-coding genes, eight rRNA genes, and 37 tRNA genes. The maximum likelihood phylogenetic analysis revealed that G. pacifica belongs to the Gypsophila group and is closely related to Dianthus within the tribe Caryophylleae.